Angiotension converting enzyme inhibition and calcium channel blockage improves cyclosporine induced glucose intolerance in rats - YAVUZ, DİLEK; TUĞLULAR, ZÜBEYDE SERHAN (ELSEVIER SCIENCE INC, 2004)
The aim of this study was to evaluate the effects of quinapril, valsartan, and amlodipin on glucose tolerance in cyclosporine (CsA)-toxic rats. Among 40 male Wistar rats 32 were administered cyclosporine (CsA) (15 mg/kg) intraperitoneally for 6 weeks. Quinapril (10 mg/kg per day) (group Q), valsartan (40 mg/kg per day) (group V), and amlodipine (10 mg/kg per day) (group A) were administered to individual sets of eight CsA-treated animals via the drinking water with the remaining untreated hosts followed as a control group (group C) and 8 healthy controls (group H). A Glucose-tolerance test was performed by administering oral glucose (2 g/kg) followed by blood samples obtained from the tail vein at baseline as well as 30,60,90, and 120 minutes after the glucose load. Glucose area under the curve (AUC) was calculated according to the trapezoidal rule. CsA levels were determined using an immunofluorescence method. Kruskal Wallis ANOVA test was used for statistical analysis. Median CsA levels were 1968 ng/mL, 1982 ng/mL, 1580 ng/mL, 1600 ng/mL; and glucose AUC, 232.4 +/- 130 mg/min per dL, 63.1 +/- 25 mg/min per dL, 115.0 +/- 90 mg/min per dL, 47.4 +/- 34 mg/min per dL 53.4 +/- 38 mg/min per dL for groups C,Q,V,A and H, respectively. Quinapril-treated and amilodipine-treated rats displayed a lower glucose AUC than group C (P < .01), which had higher glucose levels than healthy controls (P < .001). In summary, CsA treated rats show impaired glucose tolerance, which is improved by quinapril or amlodipine treatment. Angiotensin converting enzymes inhibitors and calcium channel blockers affect beta cell function rather than insulin sensitivity.
Keywords: INSULIN SENSITIVITY; TRANSPLANT RECIPIENTS; RESISTANCE; TOLERANCE; METABOLISM; PANCREAS; CELLS